Close encounters: researching intimate lives in Europe - Crowhurst, Isabel (2013)
This research note aims to extend the discussion on the methodological implications of doing research on intimacy and personal life. Drawing on a comparative study concerned with the intimate lives of those who live outside the conventional, modern western nuclear family, it reflects on the processes of gaining access to often hard-to-reach populations which informed and influenced the empirical work that we carried out in four European countries.